Formulación de las fases del plan estratégico de una empresa de consultaría en tecnología 2020-2025. (2019)
This project aims to describe the process of formulating the Strategic Plan for a technology consulting company, taking as reference the BPM-LAT organization, which manages and implements technology consulting projects in companies of the government sector in Colombia and some countries of Latinamerica. To meet the objective set, a well structured Strategic Management Scheme is used, which has the following phases: system definition, system analysis, scenario design, strategy implementation and decision making. The activities that are generated in each of the phases are carried out in conjunction with the management staff of the organization, this in order to guarantee the greatest accuracy of the data and to provide the strategies that are convenient and that best fit the Current and future needs of the company.